Back somersault-induced atrioventricular nodal reentrant tachycardia – A case of a 15-year-old promising gymnast. Issue 1 (July 2021) - Hayasaka, Taiki; Kawamura, Yuichiro; Kobayashi, Yuya; Kitani, Yuya; Hontani, Misako; Sugiyama, Eitaro; Sumitomo, Kazuhiro; Tanabe, Yasuko; Akasaka, Kazumi; Takeuchi, Toshiharu; Sato, Nobuyuki; Hirasawa, Kunihiko; et al.
Abstract: A male 15-year-old promising gymnast suffered palpitations, which emerged only after landing a round-off back somersault. The performance induced an attack of regular narrow QRS complex tachycardia that was highly reproducible. Not a single element of the performance, but a whole sequence of round-off back somersault was required to induce the attack. An electrophysiologic study revealed an intra-nodal dual pathway causing atrioventricular nodal reentrant tachycardia (AVNRT). A complication of a tiny atrial septal defect (ASD) was incidentally detected, thus we initially suspected a causal relation of ASD as the platypnea-orthodeoxia syndrome. However, it was denied as the major mechanism of attack because of a very faint shunt flow and no-induction of hypoxemia during a round-off back somersault. The major triggering mechanisms of a whole sequence of round-off back somersaults were speculated to be related to transient atrial overload and autonomic imbalance induced by a swift postural-axial change together with an intense Valsalva maneuver with the maximal level of breath holding. The AVNRT attack was successfully treated by radiofrequency catheter ablation and has never recurred even by a whole sequence of round-off back somersaults. Currently he is a healthy and active gymnast with no symptoms. <Learning objective: The individual trigger of an atrioventricular nodal reentrant tachycardia (AVNRT) attack varies. The unique and sole trigger of the attack in the present gymnast case was a whole sequence of round-off back somersaults. A swift postural-axial change together with an intense Valsalva maneuver with the maximal level of breath holding increased the atrial overload with stretching the atrial wall, which might have induced atrial extrasystole and played a trigger role initiating the AVNRT attack.>